2012
DOI: 10.1155/2012/829401
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Features ofCatha edulis(Khat) on Livers and Kidneys of Male and Female Sprague-Dawley Rats: A Subchronic Study

Abstract: Hepato- and nephrotoxicity of Khat consumption (Catha edulis Forskal) have been evoked. Therefore, this study was conducted to evaluate such possible hepatorenal toxicity in female and male Sprague-Dawley rats (SD rats) focusing primarily on liver and kidney. In addition, female and male rats were investigated separately. Accordingly, forty-eight SD-rats (100–120 g) were distributed randomly into four groups of males and female (n = 12). Normal controls (NCs) received distilled water, whereas test groups recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 37 publications
5
50
1
Order By: Relevance
“…In previous case reports, resolution of the liver injury has been recorded following cessation of khat, while relapse following reexposure has also been documented . Moreover, khat has been shown to be hepatotoxic in animals, manifesting as a spectrum of liver injury . Evidence from the present study, together with previous case reports and animal studies, supports a strong association and suggests a causal relationship between khat chewing and the development of CLD.…”
Section: Discussionsupporting
confidence: 83%
“…In previous case reports, resolution of the liver injury has been recorded following cessation of khat, while relapse following reexposure has also been documented . Moreover, khat has been shown to be hepatotoxic in animals, manifesting as a spectrum of liver injury . Evidence from the present study, together with previous case reports and animal studies, supports a strong association and suggests a causal relationship between khat chewing and the development of CLD.…”
Section: Discussionsupporting
confidence: 83%
“…Sickness behaviors such as fatigue, nausea and changes in both appetite and thirst are common symptoms of liver and kidney disease (Strid et al, 2002). Experimental evidence in Sprague-Dawley rats indicates that minor use of khat (subchronic) can lead to impaired liver and kidney functioning (Alsalahi et al, 2012). Changes in weight and leptin levels were seen after 4 weeks of use in male but not female rats but impaired renal function was evident in female but not male rats in response to subchronic use (Alsalahi et al, 2012).…”
Section: Health and Behavioral Properties Of Khat Cath And Amphmentioning
confidence: 99%
“…Experimental evidence in Sprague-Dawley rats indicates that minor use of khat (subchronic) can lead to impaired liver and kidney functioning (Alsalahi et al, 2012). Changes in weight and leptin levels were seen after 4 weeks of use in male but not female rats but impaired renal function was evident in female but not male rats in response to subchronic use (Alsalahi et al, 2012). Hepatotoxicity in this study was evident in both male and female rats.…”
Section: Health and Behavioral Properties Of Khat Cath And Amphmentioning
confidence: 99%
“…Such changes were characterized by atypical tubules, amorphous Malpighian corpuscles, and invasive infiltrative inflammatory cells. The glomerular capillaries in Malpighian corpuscles were destructed and hypertrophied [29]. In the other study, high dose Khat was shown to induce mild to moderate renal damage and significantly accentuated the gentamicin-induced renal damage in rats [30].…”
Section: Kidney Injuries Due To Herbal Medicinesmentioning
confidence: 80%